Prognostic value of base excess as indicator of acid-base balance in acute heart failure. Issue 5 (1st August 2020) - Nakano, Hiroki; Nagai, Toshiyuki; Honda, Yasuyuki; Honda, Satoshi; Iwakami, Naotsugu; Matsumoto, Chisa; Asaumi, Yasuhide; Aiba, Takeshi; Noguchi, Teruo; Kusano, Kengo; Yokoyama, Hiroyuki; Ogawa, Hisao; et al.
Abstract : Background: Acid-base balance can change as a result of pulmonary oedema and low tissue perfusion in acute heart failure patients. However, its long-term prognostic significance remains to be clarified. Methods: We prospectively examined a cohort of 472 consecutive acute heart failure patients who underwent arterial blood gas analysis on admission between January 2013 and May 2016. Acidaemia, alkalaemia and normal range of base excess were defined as pH <7.38, >7.42 and −2 to 2 mEq/L, respectively. The primary outcome was all-cause death. Results: During a median follow-up period of 714 days, 101 patients died. Although there was no difference in mortality among patients with acidaemia, normal pH and alkalaemia ( p = 0.92), patients with high base excess had the highest mortality compared with others. Multivariable Cox proportional hazard models revealed that high base excess was an independent determinant of mortality (hazard ratio 1.83, 95% confidence interval 1.08–3.13 (high versus normal base excess), hazard ratio 0.81, 95% confidence interval 0.47–1.41 (low versus normal base excess)), even after adjustment for significant prognostic covariates. Furthermore, regarding mortality stratified by base excess and carbon dioxide partial pressure (pCO2 ), patients with high base excess (>2.1 mEq/L) and high pCO2 (>40 mmHg) had the highest mortality compared with others. Conclusions: High base excess, but not low base excess, on admission was associated with long-term mortality in acute heart failure patients, indicating the importance of evaluating acid-base balance on admission by base excess for stratifying the risk of mortality in patients with acute heart failure.